Women in nursing teams: organizational identification and experiences of pleasure and suffering - Adriane Vieira; Marilia Alves; Plinio Rafael Reis Monteiro; Fernando Coutinho Garcia (Universidade de São Paulo, 2013)
OBJECTIVE: to analyze the degree of influence of the organizational identification on the experiences of pleasure and suffering of women who are members of the nursing staff of two general hospitals in Belo Horizonte. METHOD: a quantitative study was conducted with 97 nurses and 414 nursing technicians chosen by convenience in their workplaces. We used a self-administered questionnaire containing four Likert-type scales: self and hetero-perceptions; identification with the organization; and experiences of pleasure and pain at work. RESULTS: the structural relations explained a small percentage of the variability of organizational identification, showing that the self and hetero-perception are presented as relevant factors in professional identification with the organization. When considering how much the self and the hetero-perception and organizational identification all together impact in the experiences of pleasure and pain, a higher explanatory power is observed for: professional exhaustion, lack of recognition, freedom of expression and professional achievement.